The Impact of the COVID-19 Pandemic on Diagnosing and Treating Attention Deficit Hyperactivity Disorder: New Challenges on Initializing and Optimizing Pharmacological Treatment - Segenreich, Daniel (Frontiers in Psychiatry, 2022)
Introduction: COVID-19 has been causing huge disruptions in mental healthcare services worldwide, including those related to ADHD. Some consequences of the pandemic, such as virtual schooling and remote work, as well as increased telemedicine, have posed new challenges for ADHD diagnosis and treatment. In this narrative review, we summarize existing COVID-19 and ADHD literature especially focusing on ADHD diagnostic during the pandemic and aspects related to initializing and optimizing pharmacological treatment adherence as well. Methods: The following databases were searched using the broad term ‘ADHD and COVID-19’’were: PubMed, PsycINFO, EMBASE, Google Scholar and medRxiv. We included all English language articles and preprints that reported on medication/pharmacological treatment among the terms “ADHD” and “COVID-19” resulting in a total of 546 articles. The final search was done on Dec-23 2021. We selected fifteen papers articles focusing on the challenges of ADHD diagnostic during COVID-19 pandemic. Results: Of the fifteen studies included, most were cross-sectional and perspective pieces. Most of them discussed that individuals with ADHD present risk factors that may make them more vulnerable to health negative consequences of the pandemic, which in turn may have an impact onn medication treatment efficacy and adherence. Telemedicine is also addressed as a potential powerful instrument on monitoring ADHD treatment. Conclusions: Despite the challenges posed by the pandemic on monitoring ADHD treatment, the available literature stressed that the current scenario also may offer new opportunities that could lead to the development of individualized treatmentpharmacological interventions, such as the remote monitoring of symptoms.